Physicochemical Characteristics, in Vitro Fermentation Indicators, Gas Production Kinetics, and Degradability of Solid Herbal Waste as Alternative Feed Source for Ruminants - A. N. Kisworo; A. Agus; Kustantinah Kustantinah; B. Suwignyo (Faculty of Animal Science, Bogor Agricultural University, 2017)
The aims of this research were to study the nutrient and secondary metabolite contents of solid herbal wastes (SHW) that were preserved by freeze drying, sun drying and silage, as well as to analyze their effects on in vitro fermentation indicators i.e., gas production kinetics and degradability of solid herbal waste. Physical and chemical properties on three forms of SHW (sun dry, freeze dry, and silage) were characterized and then an in vitro gas production experiment was performed to determine the kinetics of gas production, methane production, NH3, microbial protein, and SHW degradability. Polyethylene glycol (PEG) was added to the three treatments to determine the biological activity of tannins. Results showed that all three preparations of SHW still contained high nutrient and plant secondary metabolite contents. Gas production, methane, NH3, microbial protein, in vitro degradability of dry matter (IVDMD) and organic matter (IVDOM) of SHW silage were lower (P<0.05) compared to sun dry and freeze dry. These results were apparently due to the high content of secondary metabolites especially tannin. It can be concluded that solid herbal wastes (SHW) can be used as an alternative feed ingredients for ruminants with attention to the content of secondary metabolites that can affect the process of fermentation and digestibility in the rumen.